2022
DOI: 10.1002/jcc.26838
|View full text |Cite
|
Sign up to set email alerts
|

Geometries, electronic structures, and bonding properties of endohedral Group‐14 Zintl clusters TM@E10 (TM = Fe, Co, Ni; E = Ge, Sn, Pb)

Abstract: The geometries, electronic structures, and bonding properties of the title endohedral Zintl clusters have been studied by using ab initio calculations. [Fe@Ge 10 ] 4À and [Co@Ge 10 ] 3À have D 5h -symmetric pentagonal prismatic structure and [Fe@Sn 10 ] 4À adopts the C 2v -symmetric structure as their ground-state structures, whereas all the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…In these previous studies, La@C 60 , which has an open-shell structure and is difficult to isolate experimentally, is theoretically predicted to be able to be stabilized by introducing CF 3 groups [56]. Then, this theoretical proposal was verified by the experimental single-crystal structure of the CF 3 -adduct of La@C 60 [57]. In the present study, we studied the addition of the trifluoromethyl group to [V@C 28 ] + to enhance its stability and facilitate its future experimental isolation.…”
Section: Emfs (Singletmentioning
confidence: 92%
See 1 more Smart Citation
“…In these previous studies, La@C 60 , which has an open-shell structure and is difficult to isolate experimentally, is theoretically predicted to be able to be stabilized by introducing CF 3 groups [56]. Then, this theoretical proposal was verified by the experimental single-crystal structure of the CF 3 -adduct of La@C 60 [57]. In the present study, we studied the addition of the trifluoromethyl group to [V@C 28 ] + to enhance its stability and facilitate its future experimental isolation.…”
Section: Emfs (Singletmentioning
confidence: 92%
“…Recently, we found that the EDA analysis could describe the bonding nature of EMFs [56] and Zintl clusters [57,58] well. Thus, to study the bonding nature between the encapsulated metal and fullerenes C 28 , we performed the EDA analysis on TM@C 28 .…”
Section: Emfs (Singletmentioning
confidence: 99%